PRDX3 is associated with metastasis and poor survival in uveal melanoma. Issue 7 (26th November 2019) - Ramasamy, Pathma; Larkin, Anne-Marie; Linge, Annett; Tiernan, Damien; McAree, Fionnuala; Horgan, Noel; Moriarty, Paul; Beatty, Stephen; Murphy, Conor C; Clynes, Martin; Kennedy, Susan; Meleady, Paula
Abstract : Aims: Uveal melanoma (UM) is the most common primary intraocular malignancy in adults, and 40% develop fatal metastatic disease. Overexpression of thioredoxin-dependent peroxidase reductase (PRDX3) has been implicated in several cancers, including prostate, breast, colorectal and lung cancer. The aim of this study was to compare the immunohistochemical expression of PRDX3 in formalin-fixed, paraffin-embedded (FFPE) primary UM tissues of patients who did and did not develop metastatic disease. Methods: Immunohistochemical staining of PRDX3 was performed on FFPE tissue microarray samples of 92 primary UM tumours from patients who did and did not develop metastatic disease. The immunohistochemical staining was assessed by two observers who were blinded to all clinicopathological and cytogenetic details including metastatic/non-metastatic information. Based on a scoring system, expression of PRDX3 was graded as high or low. Results: There were 55 tumours (59.8%) from patients who developed metastatic disease, while 37 (40.2%) were from patients who did not develop metastasis. A statistically significant difference in PRDX3 expression was observed in patients who did and did not develop metastasis (p=0.001). A significant positive correlation between high PRDX3 expression and metastasis was observed (p=0.001). A significant negative correlation between PRDX3 expression and survival was found (p=0.005). Kaplan-Meier survival analysis showed a statistically significant difference in overall survival between tumours that demonstrated low and high expression of PRDX3 (67.61 vs 130.64 months, respectively, p=0.013). Conclusions: High immunohistochemical expression of PRDX3 in primary UM tissue is associated with metastasis and poor survival.